Early postnatal dexamethasone treatment and increased incidence of cerebral palsy. Issue 3 (1st November 2000) - Shinwell, E S; Karplus, M; Reich, D; Weintraub, Z; Blazer, S; Bader, D; Yurman, S; Dolfin, T; Kogan, A; Dollberg, S; Arbel, E; Goldberg, M; et al.
Abstract : OBJECTIVE: To study the long term neurodevelopmental outcome of children who participated in a randomised, double blind, placebo controlled study of early postnatal dexamethasone treatment for prevention of chronic lung disease. METHODS: The original study compared a three day course of dexamethasone (n = 132) with a saline placebo (n = 116) administered from before 12 hours of age in preterm infants, who were ventilated for respiratory distress syndrome and had received surfactant treatment. Dexamethasone treatment was associated with an increased incidence of hypertension, hyperglycaemia, and gastrointestinal haemorrhage and no reduction in either the incidence or severity of chronic lung disease or mortality. A total of 195 infants survived to discharge and five died later. Follow up data were obtained on 159 of 190 survivors at a mean (SD) age of 53 (18) months. RESULTS: No differences were found between the groups in terms of perinatal or neonatal course, antenatal steroid administration, severity of initial disease, or major neonatal morbidity. Dexamethasone treated children had a significantly higher incidence of cerebral palsy than those receiving placebo (39/80 (49%) v 12/79 (15%) respectively; odds ratio (OR) 4.62, 95% confidence interval (95% CI) 2.38 to 8.98). The most common form of cerebral palsy was spastic diplegia (incidence 22/80 (28%) v 5/79 (6%) in dexamethasone and placebo treated infants respectively; OR 4.45, 95% CI 1.95 to 10.15). Developmental delay was significantly more common in the dexamethasone treated group (44/80 (55%)) than in the placebo treated group (23/79 (29%); OR 2.87, 95% CI 1.53 to 5.38). Dexamethasone treated infants had more periventricular leucomalacia and less intraventricular haemorrhage in the neonatal period than those in the placebo group, although these differences were not statistically significant. Eleven children with cerebral palsy had normal ultrasound scans in the neonatal period; all 11 had received dexamethasone. Logistic regression analysis showed both periventricular leucomalacia and drug assignment to dexamethasone to be highly significant predictors of abnormal neurological outcome. CONCLUSIONS: A three day course of dexamethasone administered shortly after birth in preterm infants with respiratory distress syndrome is associated with a significantly increased incidence of cerebral palsy and developmental delay.